Health-Related Quality of Life, Comorbidities, and Lifestyle Behaviors Among Survivors of Obesity-Related and Non-Obesity-Related Cancer Types - William Hernández; Génesis Rodríguez-Ortiz; Lorena González-Sepúlveda; Cynthia M. Pérez; Marievelisse Soto-Salgado; Carola T. Sánchez-Díaz (Cancers, 2026)
Background/Objectives: Obesity is a well-established risk factor for several cancers, yet few studies have explored survivorship outcomes among obesity-related cancer (ORC) survivors—a growing public health concern. Beyond cancer risk, obesity is associated with poorer health-related quality of life (HRQoL), greater comorbidity burden, and adverse lifestyle behaviors during survivorship. This study examined differences in these outcomes between ORC and non-ORC survivors living in Puerto Rico. Methods: We analyzed 569 cancer survivors aged ≥21 years actively undergoing treatment from the Impact of Social Determinants of Health on the Cancer Care Continuum in Cancer Survivors in Puerto Rico Study, with survey data collected between 2023 and 2025. ORC status was classified based on the presence of a primary ORC (n = 262); all others were classified as non-ORC (n = 307). Outcomes included: (1) HRQoL, assessed using the Functional Assessment of Cancer Therapy-General overall score and domains; (2) comorbidities; and (3) lifestyle behaviors (i.e., physical activity, alcohol use, and smoking status). Poisson regression models with robust standard errors estimated adjusted prevalence ratios (aPRs) and 95% confidence intervals (CIs) for all outcomes except smoking status and comorbidity burden, which were analyzed using multinomial logistic regression models to estimate adjusted relative risk ratios (aRRRs). Results: ORC survivors had a higher relative risk of former smoking (vs. never smoking) than non-ORC survivors (aRRR: 1.74, 95% CI: 1.02–2.96). No other differences were observed between groups. Older ORC survivors reported better emotional (aPR = 0.59, 95% CI: 0.41–0.85) and physical (aPR = 0.74, 95% CI: 0.58–0.95) well-being than older non-ORC survivors. Among male participants, ORC survivors reported a lower prevalence of moderate/exceeded drinking than non-ORC survivors. Conclusions: Findings highlight a higher relative risk of former smoking (vs. never smoking) among ORC survivors compared with non-ORC survivors, with additional sex- and age-specific patterns in alcohol use and emotional/physical well-being.